2021
DOI: 10.1111/jcmm.16384
|View full text |Cite
|
Sign up to set email alerts
|

1ɑ,25‐Dihydroxyvitamin D3 promotes osteogenesis by down‐regulating FGF23 in diabetic mice

Abstract: 1ɑ,25‐dihydroxyvitamin D3 (1,25D) and fibroblast growth factor 23 (FGF23) play important roles in bone metabolism through mutual regulation. However, the underlying mechanism between 1,25D and FGF23 in diabetes‐induced bone metabolism disorders has not yet been elucidated. In this study, we investigated the effect of 1,25D on FGF23 under diabetic condition both in vitro and in vivo. The results showed that 1,25D down‐regulated the expression of FGF23 in osteoblast significantly though a dose‐dependent manner i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Meaningfully, qRT-PCR showed that Cyp27b1 was significantly elevated in the kidneys of Ano5 KI/KI mice and a three-fold increase in Cyp27b1 mRNA accumulation was also observed in Ano5 Cys360Tyr mCOBs after 14 days of osteoblast differentiation, but not at day 0 (Figures 7F, G). Some studies have reported that calcitriol and Cyp27b1 cooperatively regulate OCN during osteogenic differentiation (43,44). Consistently, the protein levels of OCN, the most abundant non-collagenous bone matrix protein that is specifically synthesized by osteoblasts, was elevated in differentiated Ano5 KI/KI mCOBs (Figure 7H).…”
Section: Calcium-related Alternation Insupporting
confidence: 70%
See 3 more Smart Citations
“…Meaningfully, qRT-PCR showed that Cyp27b1 was significantly elevated in the kidneys of Ano5 KI/KI mice and a three-fold increase in Cyp27b1 mRNA accumulation was also observed in Ano5 Cys360Tyr mCOBs after 14 days of osteoblast differentiation, but not at day 0 (Figures 7F, G). Some studies have reported that calcitriol and Cyp27b1 cooperatively regulate OCN during osteogenic differentiation (43,44). Consistently, the protein levels of OCN, the most abundant non-collagenous bone matrix protein that is specifically synthesized by osteoblasts, was elevated in differentiated Ano5 KI/KI mCOBs (Figure 7H).…”
Section: Calcium-related Alternation Insupporting
confidence: 70%
“…It is worth noting that calcitriol is involved in calcium reabsorption and mineral deposition by activating calcium channels so as to play a vital role in bone regeneration. Calcitriol can stimulate the absorption of calcium and phosphate in the small intestine, leading to generation of optimal circumstances for matrix mineralization (43,(50)(51)(52). More and more scholars have recommended adequate 1,25(OH) 2 D 3 uptake to prevent osteoporosis, wherein its anti-aging mechanism depends on promoting matrix mineralization and preventing bone resorption (53).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang and Zanello reported that 1,25D in a dose-and time-dependent manner activates the PI3K/AKT signal by binding to VDR . To verify hypothesis that a PI3K/AKT pathway is involved in VDR anti-apoptotic functions and pretreated the cells with the PI3K inhibitor, and 1a, 25-D stimulated increases in PI3K activity were blocked by LY294002, thus confirming 1,25D binding to VDR against apoptosis through PI3K activation. , The PI3K/AKT/eNOS pathway may act as a positive regulator of endothelial NO synthase in endothelial cells and play a key role in the process of endothelial cell survival, mobilization, migration, and homing, and eNOS is a main mediator of angiogenesis. The pro-angiogenesis effect of eNOS is mediated by enhancing the expression of vascular essential factors such as NO and VEGF1–2.…”
Section: Discussionmentioning
confidence: 99%